2015
DOI: 10.1155/2015/573681
|View full text |Cite
|
Sign up to set email alerts
|

Vascular Endothelial Growth Factor in Tear Samples of Patientswith Systemic Sclerosis

Abstract: Background. Systemic sclerosis is an autoimmune disease, characterized by widespread small vessel vasculopathy, immune dysregulation with production of autoantibodies, and progressive fibrosis. Changes in levels of proangiogenic cytokines had already been determined largely in serum. Our aim was to assess the levels of VEGF in human tears of patients with SSC. Patients and methods. Forty-three patients (40 female and 3 men, mean (SD) age 61 (48–74) years) with SSc and 27 healthy controls were enrolled in this … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
16
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 22 publications
(19 citation statements)
references
References 16 publications
0
16
0
1
Order By: Relevance
“…In the eye, SyS commonly presents as dry eye, due to fibrosis of the lacrimal gland, as well as conjunctival telangiectasia and filamentous keratitis [ 158 ]. Despite these ocular manifestations, only two studies have investigated tear fluid proteomics in SyS to date [ 159 , 160 ]. In the first instance, Rentka et al [ 159 ] assessed tear fluid levels of the pro-angiogenic protein, VEGF, in 43 SyS patients and 27 healthy controls.…”
Section: Tear Fluid Analysis In Systemic Diseasesmentioning
confidence: 99%
“…In the eye, SyS commonly presents as dry eye, due to fibrosis of the lacrimal gland, as well as conjunctival telangiectasia and filamentous keratitis [ 158 ]. Despite these ocular manifestations, only two studies have investigated tear fluid proteomics in SyS to date [ 159 , 160 ]. In the first instance, Rentka et al [ 159 ] assessed tear fluid levels of the pro-angiogenic protein, VEGF, in 43 SyS patients and 27 healthy controls.…”
Section: Tear Fluid Analysis In Systemic Diseasesmentioning
confidence: 99%
“…Limited data shows no correlation between elevated serum VEGF-A with ultrasound parameters of renal vasculopathy [58]. One study has reviewed VEGF-A through non-invasive sampling of tears of SSc patients and found levels to be surprisingly low possibly explained by reduced tear secretion associated with dry eye syndrome [59].…”
Section: The Potential Role Of Vegf In Ssc Related Vasculopathymentioning
confidence: 99%
“…VEGF is one of the components of normal tear fluid [34]. Vesaluoma et al determined VEGF concentrations in healthy tears.…”
Section: Vegf In Tear Samples Of Patients With Sscmentioning
confidence: 99%
“…Parts of this chapter are reproduced from authors' recent work mentioned in the "Reference" section and properly cited in the body of the chapter (Refs. [34,36]). Permission from authors/ publishers for the usage of the content of their articles has been obtained.…”
Section: Acknowledgementsmentioning
confidence: 99%